2015
DOI: 10.1063/1.4915519
|View full text |Cite
|
Sign up to set email alerts
|

Sulphonate anchored hemicyanine dyes for dye solar cell: A study on dipole moment and polarity

Abstract: The effect of the molecular architecture of dye on the performance of a hemicyanine based dye sensitized solar cell (DSSC) has been studied using theoretical and experimental tools. These dyes were utilized as sensitizers in DSSC and then later were characterized using various techniques like I-V, impedance, electron transfer kinetics, dielectrics, and Tafel polarization in order to study the photovoltaic performance. The dye having a p-OH group (INS 1) exhibited very good photon to electricity conversion effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Hemicyanine dyes have been explored as photosensitizers in dye‐sensitized solar cells (DSSCs) because they have good photoconversion efficiency (PCEc) and are capable of producing a charge‐separated excited state through photoinduced intramolecular charge transfer. These dyes offer good PCEs via electron injection into the conduction band of wide band gap semiconductor [1] . Recent investigations show that quinolinium salts are good, mixed‐type corrosion inhibitors [2] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemicyanine dyes have been explored as photosensitizers in dye‐sensitized solar cells (DSSCs) because they have good photoconversion efficiency (PCEc) and are capable of producing a charge‐separated excited state through photoinduced intramolecular charge transfer. These dyes offer good PCEs via electron injection into the conduction band of wide band gap semiconductor [1] . Recent investigations show that quinolinium salts are good, mixed‐type corrosion inhibitors [2] …”
Section: Introductionmentioning
confidence: 99%
“…These dyes offer good PCEs via electron injection into the conduction band of wide band gap semiconductor. [1] Recent investigations show that quinolinium salts are good, mixed-type corrosion inhibitors. [2] Of particular interest are dyes and stains used in biological labeling including microscopy, chemistry, histology, cytology, and medicine as fluorescent sensors and probes, and anticancer treatments such as photodynamic therapy [3] or as electron mediators in bioelectrochemical systems.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena is known to be beneficial to the V oc of the solar cell device based on this dye . In addition, studies have shown that having a large dipole moment lead to better dye-to-TiO 2 charge transfer as a result of enriched directional flow of the electrons to the TiO 2 electrode . Therefore, a large dipole moment could aid in averting the charge recombination resulting to a high V oc .…”
Section: Resultsmentioning
confidence: 99%
“…The greater the dipole moment, the greater the polarity of the molecule. [ 248 ] The research results show that the molecular dipole moment of SCP grafted with NO 2 is the largest, reaching 5.2526 Debye. This is due to the strong polarity of NO 2 and its strong electron‐withdrawing ability, which leads to the accumulation of internal charges around NO 2 and the increase of the dipole moment.…”
Section: Strategies For Dielectric Modulation Of Cellulosic Triboelec...mentioning
confidence: 99%